Digital Entrepreneurial Marketing: Strategi Bisnis UKM dalam Mengatasi Pandemi COVID-19 - Siti Nurjanah; Triyono Arief Wahyudi (LPMP Imperium, 2020)
This activity aims to provide knowledge and motivation to local businesses in the face of the Covid-19 pandemic. In the midst of the pandemic, many business actors in East Belitung are losing money due to Covid-19. A number of business actors have stopped production because there is no demand from consumers. Consumers are more turning to the primary sector to meet their daily needs. Seeing this condition, the executor deems it necessary to hold Community Service activities. The method used in this activity is in the form of training and training on digital entrepreneurship marketing. Participants are given training with activities using online learning method of providing material and followed by a question and answer session and practice / practice; giving working papers that are filled in according to the real conditions of the participants. Participants in the activity are MSME players who are in Manggar District, East Belitung Regency. This group is part of an effort to develop local community welfare. Keywords: digital entrepreneurial marketing, business strategy